Heuristics, Protocol, and Considerations for Flow Chemistry in Photoredox Catalysis. Issue 12 (20th October 2017) - Moschetta, Eric G.; Richter, Steven M.; Wittenberger, Steven J.
Abstract: Heuristics for employing photoredox catalysts in coiled‐tube LED reactors for flow chemistry are presented. These heuristics focus on common reaction parameters (for example, reagent concentration, tube diameter and light intensity) designed to encompass as many photoredox systems as possible. A chemical actinometer based on a common photocatalyst, [Ru(bpy)3 Cl2 ], is used to determine how each parameter affects the observed rate of reaction and the photon flux received in the reactor. These heuristics are then demonstrated using a photoredox reaction to see if they accurately predict flow reaction conditions that correspond to increased rates of reaction. Abstract : Trip the light fantastic : Heuristics for implementing photoredox catalysis in coiled‐tube LED flow reactors are presented. These heuristics are intended for use in a broad range of photoredox reactions. Chemical actinometry is used to determine how changing reaction parameters affects the photon flux received in the reactor, which affects the rate of reaction. An example of applying these heuristics to a photoredox reaction is provided.